Contrasting species boundaries between sections Alternaria and Porri of the genus Alternaria. (25th August 2017) - Ozkilinc, H.; Rotondo, F.; Pryor, B. M.; Peever, T. L.
Abstract : The fungal genus Alternaria comprises a large number of asexual taxa with diverse ecological, morphological and biological modes ranging from saprophytes to plant pathogens. Understanding the speciation processes affecting asexual fungi is important for estimating biological diversity, which in turn affects plant disease management and quarantine enforcement. This study included 106 isolates of Alternaria representing five phylogenetically defined clades in two sister sub‐generic groups: section Porri ( A. dauci, A. solani and A. limicola ) and section Alternaria ( A. alternata / tenuissima and A. arborescens ). Species in section Porri are host‐specific while species in section Alternaria have wider host ranges. For each isolate, DNA sequences of three genes ( Alt a1, ATPase, Calmodulin ) were used to estimate phylogenies at the population and species levels. Three multilocus haplotypes were distinguished among A. dauci isolates and only one haplotype among A. solani and A. limicola isolates, revealing low or no differentiation within each taxon and strong clonal structure for taxa in this section. In contrast, 37 multilocus haplotypes were found among A. alternata / tenuissima isolates and 21 multilocus haplotypes among A. arborescens isolates, revealing much higher genotypic diversity and multiple clonal lineages within taxa, which is not typical of asexual reproducing lineages. A species tree was inferred using a Yule Speciation model and a strict molecular clock assumption. Species boundaries were well defined within section Porri. However, species boundaries within section Alternaria were only partially resolved with no well‐defined species boundaries, possibly due to incomplete lineage sorting. Significant association with host specificity seems a driving force for speciation.